Antifungal and Coagulation Properties of a Copper (I) Oxide Nanopowder Produced by Out-of-Phase Pulsed Sonoelectrochemistry - Mancier, Valérie; Fattoum, Sirine; Haguet, Hélène; Laloy, Julie; Maillet, Christina; Gangloff, Sophie C.; Chopart, Jean-Paul (Antibiotics, 2024)
Copper (I) oxide (cuprite) is a material widely used nowadays, and its versatility is further amplified when it is brought to the nanometric size. Among the possible applications of this nanomaterial, one of the most interesting is that in the medical field. This paper presents a cuprite nanopowder study with the aim of employing it in medical applications. With regards to the environmental context, the synthesis used is related to green chemistry since the technique (out-of-phase pulsed electrochemistry) uses few chemical products via electricity consumption and soft conditions of temperature and pressure. After different physico-chemical characterizations, the nanopowder was tested on the Candida albicans to determine its fungicide activity and on human blood to estimate its hemocompatibility. The results show that 2 mg of this nanopowder diluted in 30 µL Sabouraud broth was able to react with Candida albicans. The hemocompatibility tests indicate that for 25 to 100 µg/mL of nanopowder in an aqueous medium, the powder was not toxic for human blood (no hemolysis nor platelet aggregation) but promoted blood coagulation. It appears, therefore, as a potential candidate for the functionalization of matrices for medical applications (wound dressing or operating field, for example).
Keywords: Candida albicans; antifungal materials; copper (I) oxide; cuprite; hemostasis; nanoparticles; platelet; sonoelectrochemistry